Biomimetic dual-oriented/bilayered electrospun scaffold for vascular tissue engineering. Issue 4 (3rd March 2020) - Li, Xingmao; Huang, Lin; Li, Long; Tang, Ya; Liu, Qibin; Xie, Haibo; Tian, Jialiang; Zhou, Shaobing; Tang, Geng
Abstract: Natural blood vessels have a multi-layered, cell-specific oriented spatial structure, mimicking of this structure is a promising way for blood vessel regeneration. In this study, a newly developed dual-oriented/bilayered small-diameter tubular scaffold was electrospun using a mixture of poly (ε-caprolactone) (PCL), poly (D, L-lactide-co-glycolide) (PLGA) and gelatin. The nanofiber orientations of the bilayers were spatially perpendicular to each other, aiming at guiding cell-specific orientation of smooth muscle cells (SMCs) and endothelial cells (ECs) in vitro respectively. The results showed that the hydrophilicity of scaffold was greatly improved by gelatin, and the mechanical property of this scaffold was the best among all. The in vitro degradation demonstrated that by mixing of three biodegradable polymers, a relatively fast degradation rate was achieved. After SMCs and ECs were seeded on scaffolds, cell viability, cellular morphology, and cytoskeleton behavior were investigated. The results revealed that as-electrospun scaffolds could promote both SMCs and ECs proliferation. Moreover, topographic cues offered by oriented nanofibers could guide the growth and orientation of SMCs and ECs. Therefore, the dual-oriented/bilayered electrospun scaffold is a superior structural and functional analogue to natural blood vessel and a potential candidate for vascular tissue engineering.